Existence of positive solutions for non local p-Laplacian thermistor problems on time scales - Ammi, M.R.S. (2011)
We make use of the Guo-Krasnoselskii fixed point theorem on cones to prove existence of positive solutions to a non local p-Laplacian boundary value problem on time scales arising in many applications. © 2007 Victoria University. All rights reserved.